Mechanical Thrombectomy in Acute Stroke Patients with Moderate to Severe Pre-Stroke Disability - Marek Sykora; Patrik Michel; Davide Strambo; Stefan Krebs; Julia Ferrari; Alexandra Posekany; Dominika Mikšová; Konstantin Hermann; Thomas Gattringer; Elke Gizewski; Hannes Deutschmann; Christian Neumann; et al. (Journal of Stroke, 2022)
Background and Purpose Studies on mechanical thrombectomy (MT) in acute ischemic stroke (AIS) patients with preexisting disability are limited. We aimed to compare the outcomes of MT versus best medical treatment (BMT) in these patients. Methods In the nationwide Austrian registry and Swiss monocentric registry, we identified 462 AIS patients with pre-stroke disability (modified Rankin Scale [mRS] score ≥3) and acute large vessel occlusion. The primary outcome was returning to pre-stroke mRS or better at 3 months. Secondary outcomes were early neurological improvement (National Institutes of Health Stroke Scale score improvement ≥8 at 24 to 48 hours), 3-month mortality, and symptomatic intracerebral hemorrhage (sICH). Multivariable regression models and propensity score matching (PSM) were used for statistical analyses. Results Compared with the BMT group (n=175), the MT group (n=175) had younger age, more severe strokes, and lower pre-stroke mRS, but similar proportion of receiving intravenous thrombolysis. MT was associated with higher odds of returning to baseline mRS or better at 3 months (adjusted odds ratio [aOR], 2.5; 95% confidence interval [CI], 1.39 to 4.47), early neurological improvement (aOR, 2.62; 95% CI, 1.41 to 4.88), and lower risk of 3-month mortality (aOR, 0.29; 95% CI, 0.18 to 0.49). PSM analysis showed similar findings. MT was not associated with an increased risk of sICH (4.0% vs. 2.1% in all patients; 4.2% vs. 2.4% in the PSM cohort). Conclusions MT in patients with pre-stroke mRS ≥3 might improve the 3-month outcomes and short-term neurological impairment, suggesting that pre-stroke disability alone should not be a reason to withhold MT, but that individual case-by-case decisions may be more appropriate.